1991
DOI: 10.3349/ymj.1991.32.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Isometric and isokinetic torque curves at the knee joint

Abstract: Isometric and isokinetic torques of bilateral quadriceps and hamstrings were measured with Isokinetic Rehabilitation and Testing System (Model No. Cybex 340) on 40 normal untrained subjects, 20 males and 20 females, ranging between the ages of 23 and 35 years. The mean peak isometric and isokinetic torque values of both muscle groups showed no significant differences between dominant (right) and nondominant (left) limbs in both sexes; however there were significant differences between the male and the female. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 0 publications
7
17
0
5
Order By: Relevance
“…The torque-angle curves from our control subjects had similar shapes as reported previously for healthy adults with a quasi-bell-shaped curve for the knee extensors and torque that increased with longer muscle lengths for the knee flexors [15, 16]. …”
Section: Discussionsupporting
confidence: 58%
“…The torque-angle curves from our control subjects had similar shapes as reported previously for healthy adults with a quasi-bell-shaped curve for the knee extensors and torque that increased with longer muscle lengths for the knee flexors [15, 16]. …”
Section: Discussionsupporting
confidence: 58%
“…The findings of current study support previous observations which have reported a higher H/Q FUNC ratio in males compared with females [21,26,27]. This may be due to the proposed quadriceps dominance seen in females quadriceps and/or lower eccentric hamstring torque generating capability compared with males.…”
Section: Discussionsupporting
confidence: 90%
“…The subject was asked to relax his leg so that the passive determination of the effects of gravity on the limb and lever arm could be carried out. The MVC were determined for the knee extensors (m. quadriceps femoris) at a static knee joint angle of 60°(0°= full extension), that is, the angle at which maximal isometric torque is attained (33). Two maximal isometric attempts were performed with rest periods of 60 seconds in between.…”
Section: Experimental Designmentioning
confidence: 99%